The kite rider - McCaughrean, Geraldine (Oxford : Oxford University Press, 2002)
Set in 13th-century China, this is the gripping, adventurous, compulsive story of Haoyou, a boy who makes his way in the world by flying into the air, strapped to a huge kite. The story is full of both incredible adventure and personal drama, and has been received with universal acclaim.
Winner of the Carnegie Medal. Winner, Blue Peter 'The best book to keep forever'. Winner, Nestlé Smarties Bronze Award.
Keywords: Kites -- Fiction; Families -- Fiction; Circus -- Fiction; Mongols; China -- History -- Yuan dynasty, 1260-1368 -- Fiction